DEVELOPMENT OF FUTURE TEACHERS' METHODOLOGICAL CULTURE IN THE SYSTEM OF PROFESSIONAL EDUCATION - Olena Lavrentieva (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article deals with the issue of adequacy of formation and development of future teachers' methodological culture, taking into account modern social and cultural situation, science development level and requirements of practical teaching. The current system of preparing teachers has been analyzed, considering its gains and drawbacks. Malfunctions of the future teachers' methodological culture have been defined along with three levels of inconsistency in the problem in question. The article introduces the concept and the system of methods suggested for the development of the methodological culture of the future teachers grounded on the laws, general and specific principles as well as mainstream methodological approaches. The recommendations concerning subsequent development of the system of professional education are suggested taking into account the necessity of methodological and educational preparation of future professionals.